High Risk of Metabolic and Adipose Tissue Dysfunctions in Adult Male Progeny, Due to Prenatal and Adulthood Malnutrition Induced by Fructose Rich Diet - Alzamendi, Ana (2016)
The aim of this work was to determine the effect of a fructose rich diet (FRD) consumed by the pregnant mother on the endocrine-metabolic and in vivo and in vitro adipose tissue (AT) functions of the male offspring in adulthood. At 60 days of age, rats born to FRD-fed mothers (F) showed impaired glucose tolerance after glucose overload and high circulating levels of leptin (LEP). Despite the diminished mass of retroperitoneal AT, this tissue was characterized by enhanced LEP gene expression, and hypertrophic adipocytes secreting in vitro larger amounts of LEP. Analyses of stromal vascular fraction composition by flow cytometry revealed a reduced number of adipocyte precursor cells. Additionally, 60 day-old control (C) and F male rats were subjected to control diet (CC and FC animals) or FRD (CF and FF rats) for three weeks. FF animals were heavier and consumed more calories. Their metabolic-endocrine parameters were aggravated; they developed severe hyperglycemia, hypertriglyceridemia, hyperleptinemia and augmented AT mass with hypertrophic adipocytes. Our study highlights that manipulation of maternal diet induced an offspring phenotype mainly imprinted with a severely unhealthy adipogenic process with undesirable endocrine-metabolic consequences, putting them at high risk for developing a diabetic state.